Comparison of syphilis testing by reverse algorithm and conventional method among blood donors in a tertiary care center - Sasidharan, Athira; Bhaskaran, Ramesh; Baiju, Nithya M; Rafi, A.M; Valsan, Chithra (Panacea journal of medical sciences, 2022)
Introduction: Traditional testing algorithm for syphilis begins with screening non-treponemal test followed by confirmatory treponemal test. Reverse algorithm first screens with a treponemal test; reactive samples are then tested by Rapid plasma reagin test (RPR) which is used to assess disease activity. Discordant syphilis IgG and RPR results are resolved by a second treponemal test, Treponema pallidum hemagglutination assay (TPHA) as recommended by the Centres for Disease Control and Prevention laboratories.Aim: To evaluate the analytical performance of reverse algorithms in syphilis infection among donors in comparison with traditional methods and the prevalence of syphilis among blood donor populations.This was a cross sectional study done in the department of transfusion medicine from January 2019 to February 2020 which comprised of 8635 blood donors. After donation all the blood samples were screened for syphilis using chemiluminescent immunoassay (Vitros syphilis TPA assay) in Vitros 3600 EQ/ECIQ immunodiagnostic system and RPR (omega RPR test kit) irrespective of each other’s result.Whenever chemiluminescence immunoassay or RPR turns positive, the samples were sent for TPHA (Immutrep TPHA test kit) keeping it as the gold standard method.Results and Discussion: Among 8635 samples tested, seroreactivity of CLIA (Vitros syphilis TPA assay) was 0.25 % whereas for traditional algorithm 0.13%. Sensitivity, specificity and accuracy of reverse algorithm in comparison with traditional was 100 %, 70.6%, 78.3% and 36.4% ,75% and 65.1% respectively. In comparison with TPHA, Vitros TPA assay in reverse algorithm showed moderate agreement (k=0.56, p=0) which was statistically significant whereas RPR showed slight agreement (k=0.11, p=0.47). Negative predictive value of CLIA was 100% (p=0) which was statistically significant. Positive predictive value of reverse algorithm was 54.5% and 33.3% for traditional algorithm (p=0.04).